Subfornical Organ Mediates Sympathetic and Hemodynamic Responses to Blood-borne Pro-Inflammatory Cytokines - Wei, Shun-Guang (2013)
Pro-inflammatory cytokines play an important role in regulating autonomic and cardiovascular function in hypertension and heart failure. Peripherally administered pro-inflammatory cytokines such as tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) act upon the brain to increase blood pressure (BP), heart rate (HR) and sympathetic nerve activity. These molecules are too large to penetrate blood brain barrier (BBB), and so the mechanisms by which they elicit these responses remain unknown. We tested the hypothesis that the subfornical organ (SFO), a forebrain circumventricular organ that lacks a BBB, plays a major role in mediating the sympathetic and hemodynamic responses to circulating pro-inflammatory cytokines. Intracarotid artery (ICA) injection of TNF-α (200 ng) or IL-1β (200 ng) dramatically increased mean BP (MBP), HR and renal sympathetic nerve activity (RSNA) in rats with sham lesions of the SFO (SFO-s). These excitatory responses to ICA TNF-α and IL-1β were significantly attenuated in SFO-lesioned (SFO-x) rats. Similarly, the increases in MBP, HR and RSNA in response to intravenous (IV) injections of TNF-α (500 ng) or IL-1β (500 ng) in SFO-s rats were significantly reduced in the SFO-x rats. Immunofluorescent staining revealed a dense distribution of the p55 TNF-α receptor and the IL-1 receptor accessory protein, a subunit of the IL-1 receptor, in the SFO. These data suggest that SFO is a predominant site in the brain at which circulating pro-inflammatory cytokines act to elicit cardiovascular and sympathetic responses.